2016
DOI: 10.1097/j.pain.0000000000000586
|View full text |Cite
|
Sign up to set email alerts
|

Altered pressure pain thresholds and increased wind-up in adult patients with chronic back pain with a history of childhood maltreatment: a quantitative sensory testing study

Abstract: Childhood maltreatment (CM) has been associated with an increased risk of nonspecific chronic low back pain (nsCLBP). However, the mechanisms underlying this association are unclear. Therefore, this study considered whether distinct types of CM are accompanied by specific alterations in somatosensory function. A total of 176 subjects with nsCLBP and 27 pain-free controls (PCs) were included. The Childhood Trauma Questionnaire (CTQ) was used to categorize patients into 2 groups (abused/neglected vs nonabused/no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 125 publications
3
59
2
Order By: Relevance
“…A WUR > 1 indicates temporal summation (Rolke et al, 2006). The presence of wind-up has long been proposed as a feature of central sensitization (Nijs et al, 2014;Woolf, 2011) and has been identified in many COPCs (e.g., FM (Price et al, 2002), including TMD (Maixner, Fillingim, Sigurdsson, Kincaid, & Silva, 1998), LBP (Tesarz, Eich, Treede, & Gerhardt, 2016), endometriosis (Napadow et al, 2012), and IBS (Zhou, Price, Callam, Woodruff, & Verne, 2011)).…”
Section: Generalized Sensory Hypersensitivitymentioning
confidence: 99%
“…A WUR > 1 indicates temporal summation (Rolke et al, 2006). The presence of wind-up has long been proposed as a feature of central sensitization (Nijs et al, 2014;Woolf, 2011) and has been identified in many COPCs (e.g., FM (Price et al, 2002), including TMD (Maixner, Fillingim, Sigurdsson, Kincaid, & Silva, 1998), LBP (Tesarz, Eich, Treede, & Gerhardt, 2016), endometriosis (Napadow et al, 2012), and IBS (Zhou, Price, Callam, Woodruff, & Verne, 2011)).…”
Section: Generalized Sensory Hypersensitivitymentioning
confidence: 99%
“…When different QST modalities have been used to discriminate chronic LPB patients from healthy controls, the temporal summation showed good discriminability (fitted area under the receiver operating characteristic (ROC), 0.80) (Neziri et al, 2012) with a significant association with clinical pain severity and disability (Owens et al, 2016). Of note, the temporal summation was elevated in chronic LBP patients who had experienced emotional abuse during their childhood (Tesarz et al, 2016).…”
Section: Temporal Summationmentioning
confidence: 99%
“…In many chronic pain conditions, such as neuropathic (Nikolajsen et al, 1996;Maier et al, 2010), musculoskeletal (Staud et al, 2014;Tesarz et al, 2016), joint (Arendt-Nielsen, 2017), and visceral pain (Arendt- Nielsen, 1997;Dimcevski et al, 2007;Sherman et al, 2015), the temporal summation is significantly facilitated.…”
Section: Wind-up Like Pain (Temporal Summation) and After-dischargementioning
confidence: 99%
“…One explanation might be that psychotherapeutic attention paid to patients affected by pain had long focused mainly on cognitive-behavioral factors such as dysfunctional coping strategies and maladaptive behavioral patterns (14). This neglected the fact that emotional distress, e.g., caused by psychological trauma, can also have a central impact on the sensation and processing of pain (1517). It is well known that physical pain alongside the purely sensory experience of pain generally also comes with a significant emotional dimension (17, 18).…”
Section: Introductionmentioning
confidence: 99%